2011
DOI: 10.1111/j.1533-2500.2010.00445.x
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Sensory Testing May Predict Response to Sphenopalatine Ganglion Pulsed Radiofrequency Treatment in Cluster Headaches: A Case Series

Abstract: Pulsed radiofrequency treatment has been described as a nonablative alternative to radiofrequency thermocoagulation for the management of certain chronic pain syndromes. We present our first three patients with long-standing cluster headaches who were treated with pulsed radiofrequency to the sphenopalatine ganglion. All three patients have had cluster headaches for more than 10 years' duration and experienced minimal relief with conservative treatment. An excellent midterm effect was achieved in two of the th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
45
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(47 citation statements)
references
References 19 publications
2
45
0
Order By: Relevance
“…Two such studies have reported an association of CPM with pain reduction using transcutaneous electrical nerve stimulation in individuals with fibromyalgia 4 and pulsed radio frequency current in individuals with cluster headaches. 2 Specific to exercise, there are likely multiple mechanisms responsible for EIH, 3,8,13 and CPM could provide an additive effect as the exercise becomes painful. For example, pain is seen to increase steadily during prolonged submaximal isometric contractions.…”
mentioning
confidence: 99%
“…Two such studies have reported an association of CPM with pain reduction using transcutaneous electrical nerve stimulation in individuals with fibromyalgia 4 and pulsed radio frequency current in individuals with cluster headaches. 2 Specific to exercise, there are likely multiple mechanisms responsible for EIH, 3,8,13 and CPM could provide an additive effect as the exercise becomes painful. For example, pain is seen to increase steadily during prolonged submaximal isometric contractions.…”
mentioning
confidence: 99%
“…Two patients were symptom free up to 4 months, while the third patient experienced partial pain relief only. While the results of this study yielded mixed reviews, it demonstrated for the first time that PRF could be an acceptable alternative for patients non-responsive to conservative therapies [25]. The results of this case study have been replicated, with minimum treatment-related adverse events or complications, in other slightly larger studies [26,27].…”
Section: Review Of Clinical Datamentioning
confidence: 81%
“…Chua et al performed the first documented case series of PRF to the SPG. There were three patients with a history of cluster headaches in this study [25]. Two patients were symptom free up to 4 months, while the third patient experienced partial pain relief only.…”
Section: Review Of Clinical Datamentioning
confidence: 89%
“…Subsequently, studies have reported the efficacy of SPG‐PRF therapy for patients with CH. The available limited literature suggests that PRF of the SPG is a quick, effective, and safe approach for treating refractory CHs . In our previous study, we found that computerized tomography (CT)‐guided PRF of the SPG had an efficacy rate of 85% for treating ECHs.…”
Section: Introductionmentioning
confidence: 94%